Investigating the Potential of Alkali Metal Plumba-closo-Dodecaborate (B11H11Pb2–) Salts as Solid-State Battery Electrolytes - Hales, Thomas A.; Møller, Kasper T.; Humphries, Terry D.; D’Angelo, Anita M.; Buckley, Craig E.; Paskevicius, Mark (AMER CHEMICAL SOC, 2023)
Metal dodecaborate salts have been identified as a new class of ion conductors that are highly tunable. A [B-H] unit within the dodecaborate anion can be replaced with a Pb atom to create a dipole and anisotropy within the anion to tune the crystal structure of alkali metal salts, enhancing ion conductivity for solid-state electrolyte (SSE) applications in batteries. Li2B11H11Pb·xH2O shows superionic conductivity up to ∼7 mS cm-1 at 120 °C, proving it comparable to state-of-the-art LiCB11H12 at these temperatures. Dehydration of the Li salt occurs above 120 °C, causing changes in the crystal structure and a decrease in the ion conductivity. Na2B11H11Pb·xH2O shows modest ion conductivity (0.01 mS cm-1 at 170 °C), whereas the potassium salt shows conductivities below 1 × 10-5 mS cm-1. The B11H11Pb2- analogues are proposed to be inferior ion conductors to the CB11H12- varieties due to the divalent B11H11Pb2- anion causing stronger bonding between the cation and anion, possibly higher energy required to move from position to position within the crystal structure. Despite this, the insertion of a lead atom into the dodecaborate cage shows promise in allowing high ion conductivity in the solid state.